Clinical profile and pattern of bacterial isolates from bile aspirates of cholecystectomy patients - Goel, Shewtank; Pandey, Pooja Tripathi; Kumar, Abhay; Arora, Deval Kumar; Kumar, Nidhish; Singh, Abhishek (International Journal of Research in Medical Sciences, 2019)
Background: Antibiotic policy and appropriate antibiotic prophylaxis cannot be designed unless data is available about bacteria colonizing the bile associated with gall bladder disease. Authors aim was to assess the clinical profile and pattern of bacterial isolates from bile aspirates of cholecystectomy patients seeking care at a tertiary care teaching hospital. Methods: Patients who underwent cholecystectomy for various hepatobiliary ailments during year 2017-18 formed the study population. Bile aspirates were collected during cholecystectomy and sent to the microbiology laboratory. Ultrasonography, computed tomography and MRCP were done to confirm the gall bladder pathology before surgery. Results: Out of total eighty-six patients, bacterial growth was observed in 28 (32.56%) subjects. As per division of bile samples, maximum number of study participants (39.29%) having bactibilia were seen in Group II. Group with second highest number of patients showing bactibilia was Group III with 9 subjects (32.14%). Eight subjects (28.57%) exhibited bacterial growth in bile aspirates in Group I subjects. Three patients (10.71%) showed bile infected with multiple bacteria i.e. polymicrobial infection. The gram-negative preponderance was seen in all the three groups with Escherichia coli being most common in group I and II. Pseudomonas aeruginosa was isolated in majority of the patients in group II and III. Conclusions: It is advised that all patients undergoing cholecystectomy must have their bile aspirated during cholecystectomy and sent for microbiological examination and culture. It will help in choosing appropriate antibiotic to prevent infection.